Study Protocol for “Psilocybin as a Treatment for Anorexia Nervosa: A Pilot Study” - Spriggs, Meg J.; Douglass, Hannah M.; Park, Rebecca J.; Read, Tim; Danby, Jennifer L.; de Magalhães, Frederico J. C.; Alderton, Kirsty L.; Williams, Tim M.; Blemings, Allan; Lafrance, Adele; Nicholls, Dasha E.; Erritzoe, David; et al. (Frontiers in Psychiatry, 2021)
Background: Anorexia nervosa (AN) is a serious and life-threatening psychiatric condition. With a paucity of approved treatments, there is a desperate need for novel treatment avenues to be explored. Here, we present 1) an overview of the ways through which Public Patient Involvement (PPI) has informed a trial of psilocybin-assisted therapy for AN and 2) a protocol for a pilot study of psilocybin-assisted therapy in AN currently underway at Imperial College London. The study aims to assess the feasibility, brain mechanisms and preliminary outcomes of treating anorexia nervosa with psilocybin. Methods: 1) PPI: Across two online focus groups, eleven individuals with lived experience of AN were presented with an overview of the protocol. Their feedback not only identified solutions to possible barriers for future participants, but also helped the research team to better understand the concept of “recovery” from the perspective of those with lived experience. 2) Protocol: Over a 6-week period, twenty female participants (21-65 years old, body mass index (BMI) >15kg/m2) will receive three oral doses of psilocybin (up to 25 mg) delivered in a therapeutic environment and enveloped by psychological preparation and integration. We will work with participant support networks (care teams and an identified support person) throughout and there will be an extended remote follow-up period of 12 months. Our twofold primary outcomes are 1) psychopathology (Eating Disorder Examination) across the 6-month follow-up and 2) readiness and motivation to engage in recovery (Readiness and Motivation Questionnaire) across the 6-week trial period. Neurophysiological outcome measures will be: 1) functional magnetic resonance imaging (fMRI) brain changes from baseline to 6-week endpoint and 2) post-acute changes in electroencephalography (EEG) activity, including an electrophysiological marker of neuronal plasticity. Discussion: The results of this pilot study will not only shed light on the acceptability, brain mechanisms, and impression of the potential efficacy of psilocybin as an adjunct treatment for AN but will be essential in shaping a subsequent Randomised Control Trial (RCT) that would test this treatment against a suitable control condition. Clinical Trial Registration: NCT04505189